Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Beras Di Provinsi Aceh : Studi Kasus Kota Kuala Simpang Kab. Aceh Tamiang - Dhea Savitri; Yusrizal Yusrizal; Nuri Aslami (STIKes Ibnu Sina Ajibarang, 2023)
This research aims to identify factors that influence rice demand in Aceh Province. One of the problems with rice demand in Aceh is that the price of rice is relatively high and tends to rise as time goes by and people with higher incomes tend to have greater purchasing power, so they can buy more rice and other consumer goods. This research uses multiple linear analysis. The data used in this research is primary data from residents in Kuala Simpang City, Aceh Tamiang Regency through direct interviews by answering questions in the questionnaire. The sampling for this research was carried out by Random Sampling with a sample size of 100. The results of the analysis show that the factors that significantly influence the demand for rice are the price of goods which has a value of 2.499 (t count) > 1.984 (t table), while the variables that have no effect is the income level which has a value of 0.744 (t count) > 1.984 (t table).